NIR bacteriochlorin chromophores accessed by Heck and Sonogashira cross-coupling reactions on a tetrabromobacteriochlorin derivative. Issue 4 (16th December 2015) - de Assis, Francisco F.; Ferreira, Marco A. B.; Brocksom, Timothy J.; de Oliveira, Kleber T.
Abstract : The synthesis of a new tetrabromobacteriochlorinBCBr4 is reported. Pd cross-coupling reactions yielded tetra-coupled products with a significant red shift in the UV-Vis bands. Abstract : The synthesis of a new tetrabromobacteriochlorinBCBr4 is reported having the 3, 4-dibromo-1 H -pyrrole-2-carbaldehyde (10 ) as the major precursor. TheBCBr4 was successfully employed in Pd cross-coupling reactions with methyl acrylate, phenyl acetylene and 4-ethynylanisole. In all three cases, the desired tetra-coupled products were obtained in good to excellent yields, and present a significant red shift in the UV-Vis bands above 800 nm. DFT and TD-DFT theoretical analyses of the NIR bacteriochlorin chromophores were performed in order to evaluate the effect of β substitution on their electronic structures.